Peran Lembaga Dakwah Kampus Dalam Membina Akhlak Pada Mahasiswa Universitas Islam 45 - Sri Mulyani; Aulia Ayu Rohayah (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2024)
The purpose of this research is to determine the concept of morals and efforts to develop student morals at the Islamic University 45 Bekasi. This thesis was prepared based on field data using qualitative methods. The data collected was obtained through observation, in-depth interviews and documentation studies, while the analysis used qualitative descriptive analysis techniques, namely descriptions and descriptions of the collected data as a whole about an actual situation. The results of this research show that the campus da'wah institution at the Islamic University